The Experience Of A Batak Angkola Husband Accompanying His Wife In Providing Exclusive Breastfeeding In Padangsidempuan Cityphenomenological Study - Novita Sari Batubara,; Andi Ummu Salmah,; Rahayu Indriasari,; Wahiduddin,; Toto Sudargo,; Citrakesumasari,; Mardiana Ahmad,; Yahya,; Anto J. Hadi,; Rini Amalia Batubara,; Haslinah Ahmad,; Anwar Mallongi,; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Exclusive breastfeeding is the provision of breast milk only, without the addition of other fluids such as formula milk, water, honey, tea or other foods. The aim of this research is to explore in depth the experience of Angkola Batak husbands accompanying their wives to provide exclusive breastfeeding in the city of Padangsidempuan. The research design is phenomenological. The data collection method was carried out by in-depth interviews. The purposive sampling method was used to select participants who met the criteria as participants. The participants in this research were 10 people consisting of husbands, traditional leaders, community leaders and religious leaders in Padangsidempuan City. The transcribed interview results were analyzed using content analysis. The results of this research found 5 themes that reflect the phenomenon studied. These themes are husband's behavior regarding exclusive breastfeeding, husband's support for wives when breastfeeding, Dalihan Natolu's support for exclusive breastfeeding , cultural influence on exclusive breastfeeding, community response to husbands who help their wives during breastfeeding. It is recommended that the local government of Padangsidempuan City include the role of husbands, traditional figures, community leaders and religious leaders in the success of exclusive breastfeeding.